Recent Advancements in CRISPR-Cas9 Technology for Precision Gene Editing and Therapeutic Applications - Jayarajan, D.; Kumar Dutta, Amit; Paripuranam, T.Deborah; Krishnaveni, M.; Bhavya, S. (Journal of Neonatal Surgery, 2025)
The CRISPR-Cas9 system has emerged as a transformative tool in genetic engineering, enabling scientists to edit genomes with unprecedented precision, efficiency, and simplicity. Since its adaptation from a prokaryotic immune mechanism to a gene-editing platform, CRISPR-Cas9 has rapidly progressed from bench research to translational and clinical applications. This paper presents a comprehensive review of the most recent advancements in CRISPR-Cas9 technology, particularly focusing on innovations that enhance the accuracy, versatility, and therapeutic utility of gene editing. Key breakthroughs include the development of base editing and prime editing technologies, which allow for single-nucleotide substitutions and complex DNA insertions or deletions without creating double-stranded breaks. These tools have significantly expanded the scope of precise genetic modifications and minimized genotoxicity. Moreover, the engineering of high-fidelity Cas9 variants—such as eSpCas9, SpCas9-HF1, and HypaCas9—has markedly reduced off-target activity, thereby addressing one of the major limitations in clinical genome editing. Innovations in delivery strategies, including the use of viral vectors (e.g., AAV, lentivirus), lipid nanoparticles, and electroporation of ribonucleoprotein complexes, have improved the in vivo and ex vivo application of CRISPR-Cas9 for therapeutic purposes. Notable clinical progress has been observed in the treatment of genetic disorders such as sickle cell disease, β-thalassemia, and hereditary blindness, with several patients experiencing durable therapeutic benefits. Simultaneously, CRISPR-based immunotherapies are being explored for cancers and viral infections, such as HIV, marking a shift toward more personalized and targeted treatments. Despite these advances, challenges remain, including immune responses to Cas9 proteins, potential mosaicism in edited cells, ethical concerns regarding germline editing, and regulatory hurdles that govern clinical translation. Furthermore, the integration of computational tools, including machine learning and deep learning algorithms, has become critical for optimizing guide RNA design, predicting off-target effects, and refining editing outcomes. This integration of biotechnology and computational sciences is propelling the CRISPR field into a new era of precision medicine. In conclusion, recent advancements in CRISPR-Cas9 technology are not only pushing the boundaries of what is technically feasible in genome editing but are also laying the groundwork for safe, effective, and personalized therapeutic applications. As the technology continues to mature, it holds the promise to redefine the future of medicine, particularly in the treatment and potential cure of a wide range of genetic and complex diseases.